Amplified expression of the HER2/ERBB2 oncogene induces resistance to tumor necrosis factor alpha in NIH 3T3 cells. - Hudziak, R M (1988)
Functional characterization of oncogene products that induce cellular transformation has progressed rapidly in recent years. However, less is known about the mechanism(s) by which the transformed cells may escape destruction by host immune defenses and form tumors. A recently described oncogene that has an important association with aggressive human breast carcinoma is "HER2," for human epidermal growth factor receptor 2. The oncogene has also been called NGL and human c-erbB-2 (ERBB2). In this paper we show that amplification of HER2 oncogene expression can induce resistance of NIH 3T3 cells to the cytotoxic effects of recombinant tumor necrosis factor alpha (rTNF-alpha) or macrophages. Resistance is accompanied by an increased dissociation constant for rTNF-alpha binding to high-affinity receptors on the HER2-transformed NIH 3T3 cells. The resistance phenotype is independent of transformation since NIH 3T3 cells transformed by the activated human homologue of the Harvey-ras oncogene (HRAS) retain high-affinity binding sites for rTNF-alpha as well as sensitivity to its cytotoxic effects. These results suggest that HER2 may potentiate tumorigenesis by inducing tumor cell resistance to host defense mechanisms.